Resilient and Sustainable Farming Systems in Europe Exploring Diversity and Pathways - Meuwissen, Miranda P. M.; Feindt, Peter H.; Garrido, Alberto; Mathijs, Erik; Soriano, Bárbara; Urquhart, Julie; Spiegel, Alisa (Social Sciences, 2022)
Farming systems in Europe are rapidly evolving while at the same time being under threat. Farming systems must become more resilient in response to growing economic, environmental, institutional, and social challenges facing Europe's agriculture. This study will help determine the future and sustainability of European farming systems.